Efektivitas Pelaksanaan Audit Investigasif Dalam Mendeteksi Kecurangan Ditinjau Dari Independensi Dan Penerapan Teknik Audit Berbantuan Komputer (TABK) - Khairatul Muna; Tuti Meutia (Jurnal Riset Akuntansi, 2024)
this study was conducted to determine the effect of independency and the application of Computer-Aided Audit techniques (TABK) on the effectiveness of investigative Audit in detecting fraud. This study uses qualitative methods with literature review in previous research journals. Sources of data obtained from journals and the internet relating to independence, the application of computer-aided audit techniques, and the effectiveness of investigative audits in detecting fraud. The results showed that the independence and application of computer-aided audit techniques (TABK) have a positive effect on the effectiveness of investigative audit in detecting fraud